STUDI KELAYAKAN INDUSTRI RUMAH TANGGA MINUMAN BUAH CARICA (Studi Kasus di Desa Patakbanteng Kecamatan Kejajar Kabupaten Wonosobo) - Miftahul Janah; Renan Subantoro; -Eka Dewi Nurjayanti (MEDIAGRO, 2016)
Technological developments lead to new innovations, carica fruit beverage is one of innovation in post-harvest handling of agricultural products. The purposes of this research are to determine income level and feasibility level of carica fruit beverage household industry in Patakbanteng Village Kejajar District Wonosobo Regency. The basic method that used in research was using descriptive analytical method. Sampling was carried out purposive sampling. The total number of respondents is eight carica fruit beverage household industries. Data were collected from respondents by interviews and observations. There are two types of carica fruit beverage packaging, glass bottles and plastic cups. Each type consists of two sizes, large and small. Based on research the fixed costs is Rp 218.043,93, and the variable cost is Rp 55.129.920, so the total cost is Rp 55.347.963,93. Fixed costs consist of depreciation cost, while the variable costs consist of raw materials cost (Rp 17.271.800), labor cost (Rp 4.613.250), material packaging cost (Rp 16.353.188) and others cost (Rp 16.873.683). Total revenue is Rp191.158.500 so the income is Rp 135.810.536. Carica fruit beverage has RC Value 3,45 that means this industry is feasible. With the availability of raw materials, owners of these industry are expected to be able to optimize its production and improve product management.   Keywords: business analysis, carica fruit beverage, Patakbanteng